Validating SERVPERF model in government agencies. - Ali, Mass Hareeza; Ali, Noor Azman; Radam, Alias (2010)

(untitled)
The research measures on the service quality assessment in three research samples of tax-collecting government agencies by using customer as the respondents. Customers are vital in service organization as they are aimed at reactive targets, they are the people who are directly involved in shaping and formulating the eventual ‘product’ (Irons, 1997). Customers’ view and expectations will be used to analyze the service quality assessment in particular tax collector government agencies. The present study seeks to address the following objectives; (1) to examine the customers’ perceptions of the service provided in three tax collecting government agencies; (2) to identify and analyze the relative importance of factors contributing to the service quality offered by Malaysian tax- collecting agencies. Result from the research was expected to contribute new information in the development criteria for measurement of quality of service particularly in the tax-collecting agencies in Malaysia. It also will generate an improvement in ‘service quality’ provided by the agencies that would help to solve or act as helpful sources in making effective decisions. The result would help the agencies to improve their level of service to both their employees and customers.